Effects of moxibustion on symptoms of mild cognitive impairment: protocol of a systematic review and meta-analysis. Issue 4 (28th April 2020) - Zhang, Tao; Wang, Lin-Peng; Wang, Gui-Ling; Sun, Jing-Qing; Mao, Xue-Wen; Jiang, Hui-Li; Li, Bin; Liu, Cun-Zhi
Abstract : Introduction: Mild cognitive impairment (MCI) is considered the intermediate phase between normal age-related cognitive decline and dementia. Moxibustion has gained increased popularity for the management of MCI in China.This study aimed to evaluate the effects and safety of moxibustion on symptoms of MCI. Methods and analysis: Four English databases and six Chinese databases will be searched from their inception to October 2019: Embase, MEDLINE, Cochrane Central Register of Controlled Trials, Allied and Complementary Medicine Database, China National Knowledge Infrastructure, Chongqing VIP Chinese Science and Technology Periodical Database, Wanfang Database, SinoMed, China Doctoral Dissertations Full-text Database and the China Master's Theses Full-text Database. Only clinical randomised controlled trials and the first period in randomised cross-over trial related to moxibustion for MCI will be included. The primary outcomes include the improvement of cognitive function, as measured by validated assessment tools. The secondary outcomes include changes in the activity of daily living scale, effective rate and the incidences of adverse events. The selection of studies, data extraction and risk of bias assessment will be carried out by two independent reviewers. Review Manager V.5.3 software will be used for statistical analyses. Heterogeneity test, data synthesis and subgroup analysis will be performed if necessary. The risk of bias of included studies will be assessed by the Cochrane Handbook risk of bias tool. Evidence quality will be evaluated using the Grading of Recommendations Assessment, Development and Evaluation system. Ethics and dissemination: Ethics approval is not required as no private information from individuals are collected. The results will be published in a peer-reviewed journal or disseminated in relevant conferences. Trial registration number: CRD42018112657.